A low temperature sintered ceramic and its preparation method

By pretreating and modifying kaolin and adding abrasive agent to the preparation of ceramic blanks, the problem of high sintering temperature of daily ceramics is solved, low-temperature sintering is achieved, energy consumption and pollution are reduced, and the performance of ceramics is improved.

CN119661192BActive Publication Date: 2025-04-22FUJIAN DEHUA COUNTY PENGKUN CERAMICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510185801.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-22
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

In the prior art, the sintering temperature of daily ceramics is high, resulting in high energy consumption, long production cycle and serious pollution, and the water absorption rate of the ceramic body is too high, making it difficult to porcelain.

Method used

By pretreating and modifying the kaolin and adding special agitators to the ceramic blank preparation process, the sintering temperature of the ceramic is reduced, the sintering process is optimized, and the low-temperature sintering is achieved.

Benefits of technology

It reduces energy consumption, improves production efficiency, reduces environmental pollution, and improves the mechanical properties and wear resistance of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a method for preparing low-temperature sintered ceramics, comprising the following steps: S1, pre-treating kaolin; S2, modifying kaolin; S3, preparing a ceramic body; S4, preparing a glaze; S5, preparing a low-temperature sintered ceramic. The low-temperature sintered ceramics provided by the present invention effectively reduce the sintering temperature of the ceramics by pre-treating and modifying kaolin, and adding a special grinding aid during the preparation of the ceramic body, while optimizing the sintering process, and realizing low-temperature sintering of the ceramics, which not only reduces energy consumption, but also improves production efficiency, has significant economic benefits and environmental protection significance, and the prepared ceramics have good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of daily-use ceramics, and in particular relates to a low-temperature sintered ceramic and a preparation method thereof. Background Art

[0002] Ceramics is a general term for pottery and porcelain. People invented pottery as early as the Neolithic Age about 8,000 years ago. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but less plastic. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made from clay, a large amount of resources originally available on the earth, after quenching. Clay is tough in nature, can be plasticized when exposed to water at room temperature, can be carved when slightly dry, and can be ground when completely dry; fired to 700℃ to become pottery that can hold water; fired to 1230℃ to vitrify, which can be almost completely non-absorbent and resistant to high temperature and corrosion. Generally speaking, the ceramic production process includes three basic stages: blank manufacturing, blank forming, and porcelain sintering. At the same time, the composition of the ceramic production process can be divided into production technology preparation process, basic production process, auxiliary production process, and production service process according to the different functions of each stage of production.

[0003] Daily-use ceramics refer to ceramic products used in daily life, such as bowls, plates, cups, pots, etc., and their quality is closely related to the production process. In the traditional ceramic manufacturing process, high-temperature firing is an indispensable link, but there are problems such as high energy consumption, long production cycle, and serious pollution in the high-temperature firing process. The firing temperature of daily-use porcelain is above 1250℃, mostly between 1300℃-1400℃. The higher the temperature, the greater the unit energy consumption. Practice has proved that: reducing from 1400℃ to 1350℃ can reduce energy consumption by 10%; at the same time, the temperature reduction also increases the service life of ceramics. Therefore, using energy-saving raw materials, reducing firing temperature, and shortening firing time is an effective way to save energy and reduce consumption in the daily-use porcelain industry, which will have significant economic benefits. In recent years, low-temperature fast firing technology has been widely used in the field of ceramic manufacturing. This technology can reduce manufacturing costs, improve production efficiency, shorten firing cycles, and reduce environmental pollution.

[0004] Low-temperature fast firing technology is a new type of ceramic forming and sintering technology, also known as fast sintering technology or fast preparation technology. Compared with traditional high-temperature ceramic firing technology, the firing temperature of low-temperature fast firing technology is reduced by more than 80℃-100℃, the firing time is significantly shortened, and the product performance is the same or similar to that of products produced by traditional technology, thus achieving efficient sintering and rapid ceramic formation. However, since the general blank can only adapt to a heating rate of 100-300℃ / h, the heating rate during rapid firing can reach 800-1000℃ / h. Due to the fast heating rate, the blank is prone to defects such as deformation and cracking, so the formulated blank should have requirements such as small drying shrinkage and firing shrinkage, small thermal expansion coefficient, and good thermal conductivity.

[0005] Chinese patent application CN110483014A discloses a low-temperature fired environmentally friendly blank, an environmentally friendly ceramic blank and a preparation method thereof. The invention optimizes the formula of the ceramic blank so that the obtained ceramic blank has a small shrinkage rate and uniform density; on this basis, the invention further provides a preparation method of a low-temperature fired environmentally friendly ceramic blank, (1) mixing the raw materials according to the ceramic blank formula described in the above technical scheme to obtain a dry-pressed powder; (2) dry-pressing the dry-pressed powder to obtain a green blank; (3) pre-sintering the green blank to obtain a rough blank; (4) sintering the rough blank at a high temperature of 1000-1100°C for 10-12h to obtain a ceramic blank. The prepared ceramic blank has a shrinkage rate of 5%, a water absorption rate of 2%, and a volume density of 2.9, which meets the needs of daily-use ceramics. However, this method not only consumes a lot of energy, but also has a high firing temperature, which easily leads to excessive water absorption of the ceramic blank and failure to vitrify.

[0006] Therefore, it is of great significance to develop a low-temperature sintered ceramic in this field to reduce the sintering temperature of daily-use ceramics and improve the strength and wear resistance of ceramics. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a low-temperature sintered ceramic and a preparation method thereof. By pretreating and modifying kaolin and adding special grinding aids during the preparation of the ceramic body, the sintering temperature of the ceramic is effectively reduced. At the same time, the sintering process is optimized to achieve low-temperature sintering of the ceramic, which not only reduces energy consumption but also improves production efficiency. It has significant economic benefits and environmental protection significance. The prepared ceramic has good mechanical properties.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0010] S1. Pre-treating kaolin: adding kaolin to a zinc nitrate solution, and then adding an aluminum nitrate solution and sodium lignin sulfonate, stirring evenly, adding ammonia water, and performing a hydrothermal reaction. After the reaction is completed, filtering, washing, and drying to obtain pre-treated kaolin;

[0011] S2, modified kaolin: adding the pretreated kaolin in step S1 to isopropanol, then adding a titanate coupling agent, heating to react, filtering, washing, and drying after the reaction is completed to obtain modified kaolin;

[0012] S3, preparation of ceramic body: albite, potassium feldspar, wollastonite, modified kaolin, bentonite, clay, alumina, quartz, dolomite and grinding aid are mixed evenly, and then ball milled, sieved and impurities are removed to obtain powder; deionized water is then added and wet-milled to obtain slurry, which is then put into a mold for pressing to obtain a ceramic body;

[0013] S4, preparation of glaze: potassium feldspar, calcite, spodumene, zinc oxide, talc, borax, barium carbonate, magnesium oxide, sodium tripolyphosphate and water are mixed evenly, and wet ball milled to obtain glaze slurry;

[0014] S5. Preparation of low-temperature sintered ceramics: applying the glaze slurry in step S4 to the surface of the ceramic body in step S3 by dipping, pre-firing after drying, and sintering immediately after pre-firing to obtain low-temperature sintered ceramics.

[0015] Preferably, in step S1, the mass volume ratio of the kaolin, zinc nitrate solution, aluminum nitrate solution, sodium lignin sulfonate and ammonia water is 60-70g:300-400mL:250-350mL:20-25g:100-150g, the concentration of the zinc nitrate solution is 0.3-0.4mol / L, the concentration of the aluminum nitrate solution is 0.7-0.9mol / L, the mass concentration of the ammonia water is 20-25%, the temperature of the hydrothermal reaction is 110-120°C, and the time is 5-8h.

[0016] In the present invention, a zinc-aluminum double-layer metal oxide is generated in situ on kaolin by a hydrothermal method, and the zinc-aluminum double-layer structure can effectively prevent crack propagation, thereby enhancing the fracture resistance of the ceramic. In addition, the zinc-aluminum double-layer metal oxide can also promote liquid phase sintering and reduce the sintering temperature; at the same time, sodium lignin sulfonate is added, which can be adsorbed on the surface of ceramic particles, increase the electrostatic repulsion between particles, prevent particle agglomeration, thereby improving the fluidity and stability of the slurry, and at the same time, it also has a certain adhesiveness, which can improve the strength of the ceramic body.

[0017] Preferably, in step S2, the mass ratio of the pretreated kaolin to the titanate coupling agent is 100:4-6, the temperature of the heating reaction is 60-70° C., and the time is 1-2 h.

[0018] In the present invention, the pretreated kaolin is reacted with a titanate coupling agent, which can improve the binding property of kaolin with other raw materials on the one hand, and on the other hand, the introduced high-valent Ti metal ions can enhance the electrostatic interaction between the layered bimetallic oxide layers, stabilize the layered structure, and possibly promote liquid phase sintering, thereby further reducing the sintering temperature of the ceramic body.

[0019] Preferably, in step S3, the method for preparing the grinding aid comprises the following steps:

[0020] Calcium carbonate is added to an ethanol aqueous solution, and then γ-glycidyloxypropyltrimethoxysilane is added, and the mixture is stirred for reaction. After the reaction is completed, the mixture is filtered, and the solid product is mixed with glycerol phosphate and fatty alcohol polyoxyethylene ether and then ball-milled to obtain the grinding aid.

[0021] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution is 7:3, the mass ratio of calcium carbonate and γ-glycidyloxypropyltrimethoxysilane is 100:5-7, the stirring reaction temperature is 50-60°C, and the time is 1-2h; the mass ratio of the solid product, glycerol phosphate, and fatty alcohol polyoxyethylene ether is 100:6-8:2-4, the ball milling speed is 2000-2500r / min, and the time is 20-30min.

[0022] In the present invention, the grinding aid is based on calcium carbonate, which is reacted with γ-glycidyloxypropyltrimethoxysilane to improve the dispersibility of calcium carbonate. At the same time, the introduced silane can improve the binding property of calcium carbonate with ceramic blanks. Subsequently, the calcium carbonate is ball-milled with glycerol phosphate and fatty alcohol polyoxyethylene ether, and the organic surfactant is coated on the calcium carbonate to improve the grinding aid effect of calcium carbonate.

[0023] Preferably, in step S3, the amount of each raw material used, by weight, is: 35-40 parts of albite, 15-20 parts of potassium feldspar, 25-35 parts of wollastonite, 20-25 parts of modified kaolin, 15-20 parts of bentonite, 15-20 parts of clay, 5-10 parts of alumina, 8-12 parts of quartz, 6-9 parts of dolomite, and 3-5 parts of grinding aids, and the amount of deionized water added is 1-1.5 times the weight of the powder.

[0024] In the present invention, the addition of grinding aids can reduce the surface tension between particles, prevent particle agglomeration, promote particle dispersion, and can also play a lubricating role, reduce the friction between the ball milling medium and the particles, improve the grinding efficiency and reduce energy consumption, thereby improving the grinding efficiency; the amount of grinding aid added is within this range, so that the obtained ceramic has the best comprehensive performance. If the amount added is too little, the expected grinding aid effect cannot be achieved. If the amount added is too much, it may affect the subsequent molding and sintering processes, and even affect the performance of the ceramic.

[0025] Preferably, in step S3, the rotation speed of the ball mill is 1500-1800 r / min, and the time is 40-60 min, and the rotation speed of the wet mill is 900-1100 r / min, and the time is 30-40 min.

[0026] Preferably, in step S4, the amount of each raw material used, by weight, is: 25-30 parts of potassium feldspar, 20-25 parts of calcite, 18-22 parts of spodumene, 10-15 parts of zinc oxide, 12-16 parts of talc, 3-6 parts of borax, 5-9 parts of barium carbonate, 4-7 parts of magnesium oxide, 4-6 parts of sodium tripolyphosphate, and 40-60 parts of water; the rotation speed of the wet ball mill is 1200-1500r / min, and the time is 6-8h.

[0027] Preferably, in step S5, the pre-sintering process is: heating to 400-500°C at a heating rate of 4-5°C / min, and keeping warm for 1-2h; the sintering process is: heating to 1000-1080°C at a heating rate of 8-10°C / min, keeping warm for 2-3h, and then cooling to room temperature at a cooling rate of 5°C / min.

[0028] In the present invention, a two-stage firing process is adopted, namely, pre-firing and sintering. The temperature in the pre-firing stage is relatively low and the heating rate is relatively slow, so as to remove moisture and organic matter in the green body; the heating rate in the sintering stage is relatively fast to ensure that the green body is fully sintered and densified. The rational use of the two-stage firing system, combined with the optimization of raw materials and grinding aids, ultimately achieves low-temperature sintering of ceramics.

[0029] The present invention also protects a low-temperature sintered ceramic prepared by the method as described above.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The preparation method of low-temperature sintered ceramics provided by the present invention comprises the following steps: generating a zinc-aluminum double-layer metal oxide on kaolin in situ by a hydrothermal method; the zinc-aluminum double-layer structure can effectively prevent crack propagation, thereby enhancing the fracture resistance of the ceramic; in addition, the zinc-aluminum double-layer metal oxide can also promote liquid phase sintering and reduce the sintering temperature; at the same time, sodium lignin sulfonate is added, which can be adsorbed on the surface of ceramic particles, increase the electrostatic repulsion between particles, prevent particle agglomeration, thereby improving the fluidity and stability of the slurry, and it also has a certain adhesiveness, which can improve the strength of the ceramic body; then, the pretreated kaolin is reacted with a titanate coupling agent, which can improve the binding property of kaolin with other raw materials on the one hand, and on the other hand, the introduced high-valent Ti metal ions can enhance the electrostatic interaction between the layered bimetallic oxide layers, stabilize the layered structure, and may promote liquid phase sintering, further reducing the sintering temperature of the ceramic body.

[0032] (2) The present invention provides a method for preparing low-temperature sintered ceramics. The grinding aid added is based on calcium carbonate, which can be used as a flux to lower the melting point of the ceramic and promote particle rearrangement and densification during liquid phase sintering. It is reacted with γ-glycidyloxypropyltrimethoxysilane to improve the dispersibility of calcium carbonate. At the same time, the introduced silane can improve the binding property of calcium carbonate with the ceramic blank. Subsequently, it is ball-milled with glycerol phosphate and fatty alcohol polyoxyethylene ether, and the organic surfactant is coated on it. By fixing the grinding aid on the surface of calcium carbonate particles, the grinding aid efficiency is improved, and the negative impact of free grinding aid is reduced, thereby improving the grinding aid effect of calcium carbonate. The oil phosphate mainly plays a role of dispersion and lubrication, while the fatty alcohol polyoxyethylene ether mainly plays a role of wetting and dispersion. They work together with calcium carbonate to improve the grinding efficiency of ceramic raw materials during ball milling, refine the particles of the blank raw materials, and increase the specific surface area, thereby improving the sintering activity, reducing the sintering temperature, making the sintered body dense and not easy to form abnormal particle growth, and making the mechanical properties of the blank better.

[0033] (3) The preparation method of low-temperature sintered ceramics provided by the present invention adopts a two-stage sintering process, namely pre-sintering and sintering. The temperature in the pre-sintering stage is relatively low and the heating rate is relatively slow. On the one hand, moisture and organic matter in the green body can be removed to avoid defects such as cracking of the green body caused by rapid heating in the later stage. On the other hand, the sodium lignin sulfonate in the modified kaolin can be carbonized to form biochar, which improves the thermal conductivity of the green body and thus reduces the sintering temperature of the ceramic. The heating rate in the sintering stage is relatively fast and the green body is kept at a set high temperature for a period of time to ensure that the green body is fully sintered and densified. The heating rate, holding time and cooling rate are precisely controlled by the two-stage sintering process, and the optimization of raw materials and grinding aids is coordinated to finally achieve low-temperature sintering of the ceramic, ensuring that the ceramic is fully sintered and has stable performance. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the present invention, the titanate coupling agent is purchased from Nanjing Xuanhao New Material Technology Co., Ltd., and the model is NXH-131; the particle size of the calcium carbonate is 20-30 μm; and the fatty alcohol polyoxyethylene ether is AEO-9. Example 1

[0036] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0037] S1. Pretreatment of kaolin: 65 g of kaolin was added to 350 mL of 0.35 mol / L zinc nitrate solution, followed by 300 mL of 0.8 mol / L aluminum nitrate solution and 23 g of sodium lignin sulfonate. After stirring evenly, 130 g of 25% ammonia water was added. The mixture was hydrothermally reacted at 115° C. for 7 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain pretreated kaolin.

[0038] S2, modified kaolin: 100 g of the pretreated kaolin in step S1 was added to 800 mL of isopropanol, followed by 5 g of a titanate coupling agent, and the mixture was reacted at 65° C. for 1.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified kaolin;

[0039] S3, preparation of ceramic body: by weight, 38 parts of albite, 17 parts of potassium feldspar, 30 parts of wollastonite, 23 parts of modified kaolin, 17 parts of bentonite, 18 parts of clay, 7 parts of alumina, 10 parts of quartz, 8 parts of dolomite, and 4 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1700r / min for 50min, and after sieving and impurity removal, a powder was obtained; then 1.3 times the weight of the powder was added with deionized water, and wet milling was performed at a speed of 1000r / min for 35min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0040] S4, preparation of glaze: by weight, 28 parts of potassium feldspar, 22 parts of calcite, 20 parts of spodumene, 13 parts of zinc oxide, 14 parts of talc, 5 parts of borax, 7 parts of barium carbonate, 6 parts of magnesium oxide, 5 parts of sodium tripolyphosphate, 50 parts of water were mixed evenly, and wet ball milled at a speed of 1400 r / min for 7 hours to obtain a glaze slurry;

[0041] S5. Preparation of low-temperature sintered ceramics: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping, dry and pre-fire, the pre-fire process is: heat up to 450°C at a heating rate of 4°C / min, keep warm for 1.5h, sinter immediately after pre-fire, the sintering process is: heat up to 1050°C at a heating rate of 9°C / min, keep warm for 2.5h, then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0042] The preparation method of the grinding aid comprises the following steps:

[0043] 100 g of calcium carbonate was added to 800 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 7:3), followed by the addition of 6 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at 55° C. for 1.5 h. After the reaction was completed, the mixture was filtered, and 100 g of the solid product was mixed with 7 g of glycerol phosphate and 3 g of fatty alcohol polyoxyethylene ether, and the mixture was ball-milled at a rotation speed of 2300 r / min for 25 min to obtain the grinding aid. Example 2

[0044] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0045] S1. Pretreatment of kaolin: 60 g of kaolin was added to 300 mL of 0.3 mol / L zinc nitrate solution, followed by 250 mL of 0.7 mol / L aluminum nitrate solution and 20 g of sodium lignin sulfonate. After stirring evenly, 100 g of 20% ammonia water was added. The mixture was hydrothermally reacted at 110° C. for 8 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain pretreated kaolin.

[0046] S2, modified kaolin: add 100g of the pretreated kaolin in step S1 to 800mL of isopropanol, then add 4g of titanate coupling agent, react at 60°C for 2h, filter, wash and dry after the reaction to obtain modified kaolin;

[0047] S3, preparation of ceramic body: by weight, 35 parts of albite, 15 parts of potassium feldspar, 25 parts of wollastonite, 20 parts of modified kaolin, 15 parts of bentonite, 15 parts of clay, 5 parts of alumina, 8 parts of quartz, 6 parts of dolomite, and 3 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1500r / min for 60min, and after sieving and impurity removal, a powder was obtained; then deionized water of 1 times the weight of the powder was added, and wet milling was performed at a speed of 900r / min for 40min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0048] S4, preparation of glaze: by weight, 25 parts of potassium feldspar, 20 parts of calcite, 18 parts of spodumene, 10 parts of zinc oxide, 12 parts of talc, 3 parts of borax, 5 parts of barium carbonate, 4 parts of magnesium oxide, 4 parts of sodium tripolyphosphate, 40 parts of water were mixed evenly, and wet ball milled at a speed of 1200 r / min for 8 hours to obtain glaze slurry;

[0049] S5. Preparation of low-temperature sintered ceramics: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping, dry and pre-fire, the pre-fire process is: heat up to 400°C at a heating rate of 4°C / min, keep warm for 2h, sinter immediately after pre-fire, the sintering process is: heat up to 1000°C at a heating rate of 8°C / min, keep warm for 3h, then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0050] The preparation method of the grinding aid comprises the following steps:

[0051] 100 g of calcium carbonate was added to 800 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 7:3), and then 5 g of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted at 50° C. for 2 h. After the reaction was completed, the mixture was filtered, and 100 g of the solid product was mixed with 6 g of glycerol phosphate and 4 g of fatty alcohol polyoxyethylene ether, and the mixture was ball-milled at a rotation speed of 2000 r / min for 30 min to obtain the grinding aid. Example 3

[0052] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0053] S1. Pretreatment of kaolin: 70 g of kaolin was added to 400 mL of 0.4 mol / L zinc nitrate solution, followed by 350 mL of 0.9 mol / L aluminum nitrate solution and 25 g of sodium lignin sulfonate. After stirring, 150 g of 25% ammonia water was added. The mixture was hydrothermally reacted at 120° C. for 5 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain pretreated kaolin.

[0054] S2, modified kaolin: 100 g of the pretreated kaolin in step S1 was added to 800 mL of isopropanol, followed by 6 g of a titanate coupling agent, and the mixture was reacted at 70° C. for 1 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified kaolin;

[0055] S3, preparation of ceramic body: by weight, 40 parts of albite, 20 parts of potassium feldspar, 35 parts of wollastonite, 25 parts of modified kaolin, 20 parts of bentonite, 20 parts of clay, 10 parts of alumina, 12 parts of quartz, 9 parts of dolomite, 5 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1800r / min for 40min, and after sieving and impurity removal, a powder was obtained; then 1.5 times the weight of the powder was added with deionized water, and wet milling was performed at a speed of 1100r / min for 30min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0056] S4, preparation of glaze: by weight, 30 parts of potassium feldspar, 25 parts of calcite, 22 parts of spodumene, 15 parts of zinc oxide, 16 parts of talc, 6 parts of borax, 9 parts of barium carbonate, 7 parts of magnesium oxide, 6 parts of sodium tripolyphosphate, and 60 parts of water were mixed evenly, and wet-milled at a speed of 1500 r / min for 6 hours to obtain a glaze slurry;

[0057] S5. Preparation of low-temperature sintered ceramics: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping, dry and pre-fire, the pre-fire process is: heat up to 500°C at a heating rate of 5°C / min, keep warm for 1h, sinter immediately after pre-fire, the sintering process is: heat up to 1080°C at a heating rate of 10°C / min, keep warm for 2h, then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0058] The preparation method of the grinding aid comprises the following steps:

[0059] 100 g of calcium carbonate was added to 800 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 7:3), and then 7 g of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted at 60° C. for 1 h. After the reaction was completed, the mixture was filtered, and 100 g of the solid product was mixed with 8 g of glycerol phosphate and 2 g of fatty alcohol polyoxyethylene ether, and the mixture was ball-milled at a rotation speed of 2500 r / min for 20 min to obtain the grinding aid. Comparative Example 1

[0060] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0061] S1. Modified kaolin: 100 g of kaolin was added to 800 mL of isopropanol, followed by 5 g of titanate coupling agent, and the mixture was reacted at 65° C. for 1.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified kaolin;

[0062] S2, preparation of ceramic body: by weight, 38 parts of albite, 17 parts of potassium feldspar, 30 parts of wollastonite, 23 parts of modified kaolin, 17 parts of bentonite, 18 parts of clay, 7 parts of alumina, 10 parts of quartz, 8 parts of dolomite, and 4 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1700r / min for 50min, and after sieving and impurity removal, a powder was obtained; then 1.3 times the weight of the powder was added with deionized water, and wet milling was performed at a speed of 1000r / min for 35min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0063] S3, preparation of glaze: by weight, 28 parts of potassium feldspar, 22 parts of calcite, 20 parts of spodumene, 13 parts of zinc oxide, 14 parts of talc, 5 parts of borax, 7 parts of barium carbonate, 6 parts of magnesium oxide, 5 parts of sodium tripolyphosphate, 50 parts of water were mixed evenly, and wet ball milled at a speed of 1400 r / min for 7 hours to obtain a glaze slurry;

[0064] S4. Preparation of low-temperature sintered ceramics: Apply the glaze slurry in step S3 to the surface of the ceramic body in step S2 by dipping, and pre-fire after drying. The pre-fire process is as follows: increase the temperature to 450°C at a heating rate of 4°C / min, keep warm for 1.5 hours, and immediately sinter after pre-fire. The sintering process is as follows: increase the temperature to 1050°C at a heating rate of 9°C / min, keep warm for 2.5 hours, and then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0065] The preparation method of the grinding aid comprises the following steps:

[0066] 100 g of calcium carbonate was added to 800 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 7:3), followed by the addition of 6 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at 55° C. for 1.5 h. After the reaction was completed, the mixture was filtered, and 100 g of the solid product was mixed with 7 g of glycerol phosphate and 3 g of fatty alcohol polyoxyethylene ether, and the mixture was ball-milled at a rotation speed of 2300 r / min for 25 min to obtain the grinding aid.

[0067] Compared with Example 1, the kaolin was not pretreated in this comparative example. Comparative Example 2

[0068] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0069] S1. Pretreatment of kaolin: 65 g of kaolin was added to 350 mL of 0.35 mol / L zinc nitrate solution, followed by 300 mL of 0.8 mol / L aluminum nitrate solution. After stirring, 130 g of 25% ammonia water was added. The mixture was hydrothermally reacted at 115° C. for 7 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain pretreated kaolin.

[0070] S2, preparation of ceramic body: by weight, 38 parts of albite, 17 parts of potassium feldspar, 30 parts of wollastonite, 23 parts of pretreated kaolin, 17 parts of bentonite, 18 parts of clay, 7 parts of alumina, 10 parts of quartz, 8 parts of dolomite, 4 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1700r / min for 50min, and after sieving and impurity removal, a powder was obtained; then 1.3 times the weight of the powder was added with deionized water, and wet milling was performed at a speed of 1000r / min for 35min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0071] S3, preparation of glaze: by weight, 28 parts of potassium feldspar, 22 parts of calcite, 20 parts of spodumene, 13 parts of zinc oxide, 14 parts of talc, 5 parts of borax, 7 parts of barium carbonate, 6 parts of magnesium oxide, 5 parts of sodium tripolyphosphate, 50 parts of water were mixed evenly, and wet ball milled at a speed of 1400 r / min for 7 hours to obtain a glaze slurry;

[0072] S4. Preparation of low-temperature sintered ceramics: Apply the glaze slurry in step S3 to the surface of the ceramic body in step S2 by dipping, and pre-fire after drying. The pre-fire process is as follows: increase the temperature to 450°C at a heating rate of 4°C / min, keep warm for 1.5 hours, and immediately sinter after pre-fire. The sintering process is as follows: increase the temperature to 1050°C at a heating rate of 9°C / min, keep warm for 2.5 hours, and then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0073] The preparation method of the grinding aid comprises the following steps:

[0074] 100 g of calcium carbonate was added to 800 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 7:3), followed by the addition of 6 g of γ-glycidyloxypropyltrimethoxysilane, and the mixture was stirred at 55° C. for 1.5 h. After the reaction was completed, the mixture was filtered, and 100 g of the solid product was mixed with 7 g of glycerol phosphate and 3 g of fatty alcohol polyoxyethylene ether, and the mixture was ball-milled at a rotation speed of 2300 r / min for 25 min to obtain the grinding aid.

[0075] Compared with Example 1, in this comparative example, sodium lignin sulfonate and titanate coupling agent were not introduced into kaolin. Comparative Example 3

[0076] A method for preparing low-temperature sintered ceramics comprises the following steps:

[0077] S1. Pretreatment of kaolin: 65 g of kaolin was added to 350 mL of 0.35 mol / L zinc nitrate solution, followed by 300 mL of 0.8 mol / L aluminum nitrate solution and 23 g of sodium lignin sulfonate. After stirring evenly, 130 g of 25% ammonia water was added. The mixture was hydrothermally reacted at 115° C. for 7 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain pretreated kaolin.

[0078] S2, modified kaolin: 100 g of the pretreated kaolin in step S1 was added to 800 mL of isopropanol, followed by 5 g of a titanate coupling agent, and the mixture was reacted at 65° C. for 1.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified kaolin;

[0079] S3, preparation of ceramic body: by weight, 38 parts of albite, 17 parts of potassium feldspar, 30 parts of wollastonite, 23 parts of modified kaolin, 17 parts of bentonite, 18 parts of clay, 7 parts of alumina, 10 parts of quartz, 8 parts of dolomite, and 4 parts of grinding aids were mixed evenly, and then ball milled at a speed of 1700r / min for 50min, and after sieving and impurity removal, a powder was obtained; then 1.3 times the weight of the powder was added with deionized water, and wet milling was performed at a speed of 1000r / min for 35min to obtain a slurry, which was then put into a mold for compression molding to obtain a ceramic body;

[0080] S4, preparation of glaze: by weight, 28 parts of potassium feldspar, 22 parts of calcite, 20 parts of spodumene, 13 parts of zinc oxide, 14 parts of talc, 5 parts of borax, 7 parts of barium carbonate, 6 parts of magnesium oxide, 5 parts of sodium tripolyphosphate, 50 parts of water were mixed evenly, and wet ball milled at a speed of 1400 r / min for 7 hours to obtain a glaze slurry;

[0081] S5. Preparation of low-temperature sintered ceramics: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping, dry and pre-fire, the pre-fire process is: heat up to 450°C at a heating rate of 4°C / min, keep warm for 1.5h, sinter immediately after pre-fire, the sintering process is: heat up to 1050°C at a heating rate of 9°C / min, keep warm for 2.5h, then cool to room temperature at a cooling rate of 5°C / min to obtain low-temperature sintered ceramics.

[0082] The grinding aid is calcium carbonate.

[0083] Compared with Example 1, the grinding aid in this comparative example is calcium carbonate.

[0084] The ceramics prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the morphology and surface effects of the ceramics were observed. The flexural strength was tested according to the standard GB / T 6569-2006; the fracture toughness was tested according to the standard GB / T23806-2009; the water absorption rate test: 5 pieces of ceramic product fragments were taken, washed and dried, and weighed respectively, and then the ceramic product fragments were separated and placed in distilled water, boiled for 3 hours, during which the water surface was kept above the ceramic product fragments by more than 10 mm, and then the ceramic product fragments were fished out, and the water attached to the surface of the ceramic product fragments was wiped off with a cloth saturated with water, and their weights were quickly weighed respectively, and the average water absorption rate of the 5 ceramic product fragments was calculated to obtain the water absorption rate of the ceramic product. The test results are shown in Table 1 below.

[0085] Table 1

[0086]

[0087] As can be seen from Table 1 above, the low-temperature sintered ceramics prepared by the present invention have no surface deformation and a smooth appearance under lower firing temperature and shorter firing time, and have good mechanical properties and low water absorption, and have good application prospects.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing low-temperature sintered ceramics, characterized in that: The following steps are involved: S1, adding kaolin to zinc nitrate solution, then adding aluminum nitrate solution and sodium lignin sulfonate, stirring evenly, adding ammonia water, and performing hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain pretreated kaolin; S2, adding the pretreated kaolin in step S1 to isopropanol, then adding a titanate coupling agent, heating to react, filtering, washing, and drying after the reaction is completed to obtain modified kaolin; S3, mixing albite, potassium feldspar, wollastonite, modified kaolin, bentonite, clay, alumina, quartz, dolomite and grinding aids uniformly, then ball milling, sieving and removing impurities to obtain powder; then adding deionized water, wet grinding to obtain slurry, then putting it into a mold for pressing to obtain a ceramic body; S4, mixing potassium feldspar, calcite, spodumene, zinc oxide, talc, borax, barium carbonate, magnesium oxide, sodium tripolyphosphate and water uniformly, and performing wet ball milling to obtain a glaze slurry; S5, applying the glaze slurry in step S4 to the surface of the ceramic body in step S3 by dipping, pre-firing after drying, and sintering immediately after pre-firing to obtain low-temperature sintered ceramics; In step S1, the mass volume ratio of kaolin, zinc nitrate solution, aluminum nitrate solution, sodium lignin sulfonate and ammonia water is 60-70g:300-400mL:250-350mL:20-25g:100-150g, the concentration of zinc nitrate solution is 0.3-0.4mol / L, the concentration of aluminum nitrate solution is 0.7-0.9mol / L, the mass concentration of ammonia water is 20-25%, and the hydrothermal reaction is carried out. The corresponding temperature is 110-120°C and the time is 5-8h; in step S2, the mass ratio of the pretreated kaolin and the titanate coupling agent is 100:4-6, the temperature of the heating reaction is 60-70°C, and the time is 1-2h; in step S5, the sintering process is: heating to 1000-1080°C at a heating rate of 8-10°C / min, keeping warm for 2-3h, and then cooling to room temperature at a cooling rate of 5°C / min.

2. The preparation method according to claim 1, characterized in that: In step S3, the method for preparing the grinding aid comprises the following steps: Calcium carbonate is added to an ethanol aqueous solution, and then γ-glycidyloxypropyltrimethoxysilane is added, and the mixture is stirred for reaction. After the reaction is completed, the mixture is filtered, and the solid product is mixed with glycerol phosphate and fatty alcohol polyoxyethylene ether and then ball-milled to obtain the grinding aid.

3. The preparation method according to claim 2, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution is 7:3, the mass ratio of the calcium carbonate and γ-glycidyloxypropyltrimethoxysilane is 100:5-7, the temperature of the stirring reaction is 50-60°C, and the time is 1-2h; the mass ratio of the solid product, glycerol phosphate, and fatty alcohol polyoxyethylene ether is 100:6-8:2-4, the rotation speed of the ball mill is 2000-2500r / min, and the time is 20-30min.

4. The preparation method according to claim 1, characterized in that: In step S3, the amount of each raw material is as follows, by weight: 35-40 parts of albite, 15-20 parts of potassium feldspar, 25-35 parts of wollastonite, 20-25 parts of modified kaolin, 15-20 parts of bentonite, 15-20 parts of clay, 5-10 parts of alumina, 8-12 parts of quartz, 6-9 parts of dolomite, and 3-5 parts of grinding aids. The amount of deionized water added is 1-1.5 times the weight of the powder.

5. The preparation method according to claim 1, characterized in that: In step S3, the rotation speed of the ball mill is 1500-1800 r / min, and the time is 40-60 min. The rotation speed of the wet mill is 900-1100 r / min, and the time is 30-40 min.

6. The preparation method according to claim 1, characterized in that: In step S4, the amount of each raw material is as follows, by weight: 25-30 parts of potassium feldspar, 20-25 parts of calcite, 18-22 parts of spodumene, 10-15 parts of zinc oxide, 12-16 parts of talc, 3-6 parts of borax, 5-9 parts of barium carbonate, 4-7 parts of magnesium oxide, 4-6 parts of sodium tripolyphosphate, and 40-60 parts of water; the rotation speed of the wet ball mill is 1200-1500r / min, and the time is 6-8h.

7. The preparation method according to claim 1, characterized in that: In step S5, the pre-sintering process is: heating the temperature to 400-500°C at a heating rate of 4-5°C / min and keeping the temperature for 1-2h.

8. A low-temperature sintered ceramic prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Low-temperature sintered environment-friendly blank material, environment-friendly ceramic blank and preparation method of the environment-friendly ceramic blank

    CN110483014A

  • Plastic alloy as well as preparation method and application thereof

    CN102040773A

  • Ceramic artware and preparation method thereof

    CN113087506A

  • Preparation method of ceramic insulator

    CN119330596A